Analisis Kelayakan Usaha Pemasaran Udang Windu pada CV. Surya Indah Perkasa Kabupaten Berau - Rahmad Hidayat; Muhammad Syafril; Nurul Ovia Oktawati (Medan Resource Center, 2022)
The purpose of this study was to measure the amount of net loss/profit resulting from the tiger prawn marketing business and to measure the feasibility based on the indicators of RCR, BEP, and Payback Period, as well as ROI. The types of data collected are primary and secondary according to the research objectives. The sampling technique used was the purposive sampling method with 6 selected samples. The results of this study indicate that the total net profit obtained is Rp. 35,213,401 during the production period in February 2022. The business financial feasibility analysis has an RCR value of 1.04, a production BEP of 676kg, a price BEP of Rp. 98,021, a sales BEP of Rp. 917,039.983, and a payback period of 7 years and 15 days, and the ROI value is 14%, so the effort on CV. Surya Indah Perkasa deserves to be continued.